2016
DOI: 10.1021/acs.jpcc.6b02343
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Delocalization in H2OBPc1–xMOBPcx (M = Co, Cu, Ni, Mn) Crystalline Thin-Film Organic Alloys

Abstract: Novel solution-processing deposition techniques in tandem with chemical synthesis design of small-molecule soluble derivatives represent a viable avenue for exploring organic analogues of semiconductor alloyed systems, where excitonic properties are tunable through alloy concentration. Here these properties are explored using absorption, grazing incidence X-ray diffraction (GIXRD), and temperature-dependent/time-resolved photoluminescence spectroscopy (TRPL) in a series of crystalline thin film alloys of metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 82 publications
(139 reference statements)
2
9
0
Order By: Relevance
“…Figure c shows that the PL main peak intensity increases with the decreasing temperature. Similar results could be found in our previous research, which involves H 2 -OBPc, its “cousin” derivative H 2 -PcOC 8 , , and organic alloy compounds . As discussed earlier, no obvious transition dipole rotation is observed with the increasing temperature.…”
Section: Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Figure c shows that the PL main peak intensity increases with the decreasing temperature. Similar results could be found in our previous research, which involves H 2 -OBPc, its “cousin” derivative H 2 -PcOC 8 , , and organic alloy compounds . As discussed earlier, no obvious transition dipole rotation is observed with the increasing temperature.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Our preliminary confocal Raman study on the PW thin films indicate that all these vibrational modes, including the low-energy phonons, are clearly present in these films (see Figure S8). At low temperature (below 175 K), the exciton coupling with localized molecular vibrations is suppressed, while the low-energy phonon coupling assists the delocalized exciton-polaron formation and results in the spreading of the wavefunction over the π-stacked molecular chain. ,,, Manning et al estimate the spatial extent of the delocalized exciton along the stacking axis in H 2 -OBPc system to be at least 10 lattice units. Such delocalization of the lowest-energy exciton could also be found in pentacene systems .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, in addition to the four a bands, these excitons also involve other states associated with bands in the b–e blocks, which show particularly strong dispersion along the π-stacking direction. Other theoretical studies ,, have reported that in some organic molecular crystals, charge-transfer excitons (with charge delocalized on the first neighboring molecules) can be present and can be involved in optical and transport processes; nonetheless, those crystals are made of very different, rodlike molecules such as oligoacenes and display a completely different crystal packing. More recently, highly delocalized excitons are demonstrated by experimental observations in phthalocyanines, a class of molecules similar to porphyrins, where delocalization over >10 molecules along the π-stacking direction is observed in highly crystalline samples with a low degree of compositional disorder, like ours, thus lending support to the results discussed here.…”
supporting
confidence: 88%